Acanthocephalan parasites in the striped mojarra (Eugerres plumieri) (Cuvier, 1830) of the Tamiahua Lagoon, Veracruz, Mexico Acantocéfalos parásitos de la mojarra rayada Eugerres plumieri (Cuvier, 1830) en la laguna de Tamiahua, Veracruz, México - Zarza Meza, Eduardo Alfredo; Alvarado, Juan Irvin Rodríguez; González, y Rodrigo Cuervo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Striped mojarra is a species of great economic importance as is a fishing resource for which the object of this study isto determine what are major parasites which presents, for this is captured and analyzed a total of 105 copies ofEugerres plumieri of the month of October 2013 to the month of March 2014, with a sex ratio of females and 1.44:1males, females with a size and weight average of 24.05 cm and 178.41 g and males 24,22 cm and 192.09 g, only 21.9% of the total sample was found to be parasitized, registering 207 parasites, identifying to Octospiniferoides sp andDollfusentis chandleri, females being the most parasitized by both species of acanthocephala. The rear segment ofthe intestine presented many parasites, followed by the segment average and above. In the month of October therewas an increased presence of parasites (7.5 parasites per fish) and in February found no parasites. In terms of theparameters of infection Octospiniferoides sp presented the highest prevalence (21.90%), medium (1.68 parasites perfish) and mean abundance (7.69 parasites per fish). The species Dollfusentis chandleri had individuals with anaverage of 4.31 mm